Policy Innovation Model in Developing Child-Friendly Islamic Boarding Schools: An Islamic Education Management Perspective - Qusairi, Ahmad; Wahyudi, Ikmal; Khadaifillah, Ach (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Formulating a child-friendly Islamic boarding school system (pesantren) has become a crucial challenge in today’s Islamic education, especially in addressing the conflict between traditional hierarchical disciplinary culture and the growing demands of child rights-oriented education. The purpose of this paper is to examine how innovation in policymaking is used to achieve child-friendly pesantren education. This research employs a qualitative multiple case study design, involving three Islamic boarding schools in Pasuruan Regency, Indonesia, selected as information-rich and representative cases of ongoing institutional transformation. Data were collected through in-depth interviews with 18 informants (leaders, teachers, students, and external stakeholders); observation; and document analysis, using an interactive qualitative data analysis model. The results show that policy innovation in child-friendly pesantren does not unfold in a straight line or through an administrative process; rather, it occurs through a socio-organizational ecosystem. This ecosystem is composed of the dynamic interaction among four interconnected elements: leadership, student participation, organizational culture transformation, and stakeholder support. Leadership operates through religious-symbolic legitimacy and gradual communication; stakeholder engagement reinforces institutional capacity; cultural adaptation mediates the integration of humanistic values within disciplinary traditions; and student participation sustains inclusive practices. This study enhances the discourse by introducing a socio-organizational ecosystem model of policy innovation in faith-based education, which expands current policy innovation frameworks by integrating religious legitimacy and cultural negotiation as fundamental dimensions. These findings offer theoretical and practical guidance in developing sustainable child-friendly policy innovations in Islamic boarding schools.